EFFECT OF CHICORIUM INTYBUS EXTRACT ON HISTOLOGICAL CHANGES IN LIVER AND KIDNEY OF HYPERCHOLESTEROLEMIC RABBITS - Nawras A. Alwan (Basrah Journal of Veterinary Research)
In this study, the experiment was designed to investigate the effect of daily oral administration of (0.5gm/kg. B.W) of chicory (Chicorium intybus) for one month on weight and histology of kidney and liver of hypercholesterolemic rabbits (induced by oral administration of 0.5 gm/kg of cholesterol dissolved in 3ml Soya bean oil) and compared this effect with medicial therapy used for atherosclerosis treatment . The results revealed a significant increase (P